Misinfodemic and cyberchondria experiences among Indians during COVID-19 pandemic - Vysakh C; Dr Rajendra Babu H (International Journal of Information Science and Management, 2022)
The outbreak of the COVID-19 pandemic has fuelled the surge of various kinds of misinformation, hoax, conspiracy theories and rumours which have challenged the health systems all over the globe. The present study explored how Indians responded to the Misinfodemic, as a notice as well as an information sharer during the deadly pandemic. The study also elucidated the cyberchondria experiences among the Indians due to the misinfodemic. An online survey questionnaire was used to identify the respondents and to collect the needed data for the study (N=266). The result showed that the majority of the participants noticed misinformation regarding the outbreak on various internet platforms predominantly social media. The misinformation led the participants to a spectrum of mental health issues like stress, anxiety, anger, insomnia and depression. 9.80% of participants admitted themselves sharing misinformation regarding the outbreak and men did more compared to females (16.9% to 9.2%) (t143.006 = 1.572, p =.001). The misinfodemic resulted in increasing the health anxiety of the participants and there was no significant difference among the gender in experiencing health anxiety. The findings of the study provide functional insights for advancing communication research through misinformation correction and misperception management during these kinds of unknown (medicine and treatment) pandemic situations. https://dorl.net/dor/20.1001.1.20088302.2022.20.3.15.2